2003
DOI: 10.1373/49.10.1651
|View full text |Cite
|
Sign up to set email alerts
|

Blood Loss from Laboratory Tests

Abstract: Background: Laboratory tests can be an important source of blood loss in hospitals, especially for newborns and patients in intensive care. The aim of this study was to quantify blood loss for laboratory diagnostic tests in a large number of patients in a teaching hospital. Methods: We estimated blood loss by multiplying the number and volumes of sampling tubes collected from 2654 adult inpatients. We compared the number of tests per patient for all inpatients and intensive care unit patients during the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 12 publications
2
40
0
Order By: Relevance
“…For several reasons, excessive laboratory testing may represent an economic burden for the hospital and an unnecessary risk for patients. The reasons include unnecessary cost to the healthcare system and unnecessary discomfort and blood loss to the patient 14. Although laboratory testing may deliver information to providers about a patient's internal body processes to help identify and treat a wide variety of medical conditions, repeated testing in the setting of clinical stability is not indicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For several reasons, excessive laboratory testing may represent an economic burden for the hospital and an unnecessary risk for patients. The reasons include unnecessary cost to the healthcare system and unnecessary discomfort and blood loss to the patient 14. Although laboratory testing may deliver information to providers about a patient's internal body processes to help identify and treat a wide variety of medical conditions, repeated testing in the setting of clinical stability is not indicated.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study showed that residents' cost awareness can be increased through comprehensive visual displays 14. However, that study did not specifically address whether increased awareness resulted in residents changing their clinical decision-making habits or their test ordering.…”
Section: Discussionmentioning
confidence: 99%
“…As patients remain in the ICU and more laboratory tests are obtained, transfusions will be administered that could very likely be spared with a conservative laboratory testing strategy. In a similar analysis, Wisser et al (30) were able to identify subgroups of patients who received sufficient blood tests to have specifically required blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9]12 It is likely that the volume of blood removed from patients with short stays was not clinically significant. One factor in this may have been related to the location of the study in a community hospital rather than the teaching hospital setting.…”
Section: Discussionmentioning
confidence: 99%